Motivation, basic psychological needs and intention to be physically active after a gamified intervention programme. (May 2022) - Fernandez-Rio, Javier; Zumajo-Flores, Marc; Flores-Aguilar, Gonzalo
The aim of the present study was to compare the possible effects of a gamified programme and a traditional instructional approach in secondary physical education at the level of intrinsic motivation, autonomy satisfaction, competence satisfaction, relatedness satisfaction, and intention to be physically active. A total of 54 year-nine students (14 ± 0.1 years) enrolled in two classes in the same high school participated. The school administration (totally anonymous to the study) distributed all the students among the two classes and the research team randomly considered one the experimental group ( n  = 27, 13 boys, 14 girls), which experienced a gamified learning unit, and the other the comparison group ( n  = 27, 15 boys, 12 girls), which followed a traditional instructional approach. Both study groups had the same physical education teacher with training and experience on several pedagogical approaches, including gamification. The study followed a pre-test, post-test quasi-experimental research design (the time lag between pre-test and post-test was nine weeks). The results showed significant differences at post-tests favouring the experimental group in all the variables assessed. In conclusion, the results from the present study provided support for the use of gamification in physical education since it was associated with increased levels of students' intrinsic motivation, basic psychological needs and intention to be physically active more than a traditional approach. Therefore, gamification could be considered a positive pedagogical framework for secondary physical education. Nevertheless, more studies with larger variability in contexts, participants and content are needed.